Perda de carga em mangueiras gotejadoras novas e usadas - Neto, Jayme Laperuta [UNESP]; Cruz, Raimundo Leite [UNESP]; Filho, Jayme Laperuta [UNESP]; Pletsch, Thalita Aparecida [UNESP] (My University, 2011)
This paper aims to determine the importance of emitter ́s local head loss in the hydraulic design of hose drip lines, as well as comparing the result of equations that calculate the local head loss; besides verifying the influence of iron precipitated at the hose head loss made in Brazil. The result found that localized head loss represents 23% of the total head loss; the equations showed significant results and the total head loss increased in an average of 20% after the irrigation system was used with water rich in iron.

O presente trabalho teve como objetivo determinar a importância da perda de carga localizada de um emissor tipo gotejador no dimensionamento da linha lateral, bem como comparar os resultados das equações que calculam a perda de carga localizada, além de verificar a influência de precipitados férricos, na perda de carga de uma mangueira gotejadora fabricada no Brasil. Como resultado obteve-se que a perda de carga representou 23% da perda de carga total, as equações apresentaram resultados significativos e a perda de carga aumentou em média 20% após o uso do sistema com água rica a em ferro.
Head loss in used and new hose drip lines
Keywords: Drip irrigation; Local head loss; drip irrigation; hydraulic structure; iron; irrigation system; Brazil